Quantitative trait locus mapping for important yield traits of a sorghum-sudangrass hybrid using a high-density single nucleotide polymorphism map - Lu, Qianqian; Yu, Xiaoxia; Wang, Huiting; Yu, Zhuo; Zhang, Xia; Zhao, Yaqi (Frontiers in Plant Science, 2022)
A thorough understanding of the genetic mechanisms of yield traits in sorghum-sudangrass hybrids are essential to improve their yield. To clarify the genetic regularities among the traits of sorghum-sudangrass hybrids, the F2 population was obtained by bagging and selfing in the F1 generation using ‘scattered ear sorghum’ and ‘red hull sudangrass’. It combines the characteristics of strong resistance of parents, high yield, good palatability, and has obvious heterosis. An ultra-high-density genetic linkage map based on single nucleotide polymorphism (SNP) markers was previously constructed by our team, which was used to conduct quantitative trait locus (QTL) mapping for plant height (PH), stem diameter (SD), tiller number (TN), leaf number (LN), leaf length (LL), leaf width (LW) and fresh weight (FW) of each plant in three different environments, along with their average values (AV). A total of 55 QTLs were detected, uniformly distributed over the 10 linkage groups, with limit of detection (LOD) values ranging between 2.5—7.1, which could explain the 4.9%—52.44% phenotypic variation. Furthermore, 17 yield-related loci were relatively high-frequency QTL (RHF-QTLs ) repeatedly detected in at least two environments, with an explanatory phenotypic variation of 4.9%—30.97%. No RHF-QTLs were associated with the TN. The genes within the confidence interval of RHF-QTL were annotated, and seven candidate genes related to yield traits were screened. Three QTL sites overlapping or adjacent to previous studies were detected by comparative analysis. In addition, we also found that QTL was enriched, and that qLL-10-1 and qFW-10-4 were located at the same location of 25.81 cM on LG10. The results of this study lay the foundation for QTL fine-mapping, candidate gene cloning, and molecular marker-assisted breeding of sorghum-sudangrass hybrids.